Assessment of total antioxidant capacity and antimicrobial activity of Glycyrrhiza glabra in saliva of HIV-infected patients - Eby Aluckal; Asif Ismail; Anoopa Paulose; Sanju Lakshmanan; M S Balakrishnan; Benoy Mathew; M Vikneshan; Abraham Kunnilathu (Wolters Kluwer Medknow Publications, 2017)
Objectives: The objectives of this study were to evaluate the antimicrobial activity and total antioxidant capacity (TAC) of licorice in Saliva of HIV/AIDS patients. Materials and Methods: Saliva specimens were collected from 20 people living with HIV infection, with CD4 count <500 cells/mm3 from people infected with HIV/AIDS in Mangalore city, India. A combination of amoxicillin-clavulanic acid and nystatin was taken as the positive control and normal saline as negative control. Results were compared using one-way analysis of variance followed by Tukey's post hoc analysis in SPSS 19. Results: The TAC was evaluated spectrophotometrically at 695nm using the phosphomolybdenum method. Glycyrrhiza glabra showed a statistically significant reduction (P < 0.05) in total Candida count. The TAC of G. glabra was found to be 4.467 mM/L. Conclusions: G. glabra extracts showed good anticandidal activity and also high antioxidant property which reduces the oxidative stress of HIV-infected people.